2013
DOI: 10.1002/ab.21474
|View full text |Cite
|
Sign up to set email alerts
|

The Five‐Factor Model of Impulsivity‐Like Traits and Emotional Lability in Aggressive Behavior

Abstract: Factors that increase automatic psychological processes may result in impulsive action and, consequently, aggressive behavior. The current cross-sectional study examined the association between the five-factor model of impulsivity-like traits (negative urgency, positive urgency, premeditation, perseverance, and sensation seeking), emotional lability, and physically aggressive behaviors among college students (n = 481) in a negative binomial hurdle model. In the logistic portion of the model, emotional lability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…It is reasonable that such difficulties may have disrupted their general coping abilities, increasing the likelihood of emotional, rash responses to other stressors (e.g., violence). Indeed, urgency was positively associated with benzodiazepine dependence, and has been implicated in negative substance use outcomes (Coskunpinar et al, BENZODIAZEPINES AND VIOLENT CRIME 13 2013) and as impacting the link between emotional lability and violence (Dvorak et al, 2013). Found in our study to relate to general offending, it is possible that in the context of problematic benzodiazepine use urgency may heighten the risk of violent behaviour.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…It is reasonable that such difficulties may have disrupted their general coping abilities, increasing the likelihood of emotional, rash responses to other stressors (e.g., violence). Indeed, urgency was positively associated with benzodiazepine dependence, and has been implicated in negative substance use outcomes (Coskunpinar et al, BENZODIAZEPINES AND VIOLENT CRIME 13 2013) and as impacting the link between emotional lability and violence (Dvorak et al, 2013). Found in our study to relate to general offending, it is possible that in the context of problematic benzodiazepine use urgency may heighten the risk of violent behaviour.…”
Section: Discussionmentioning
confidence: 55%
“…General sensation seeking tendencies may also impact this response, by impacting activity and environment selection, and level of forethought of actions. Found to be higher in violent offenders in our study, sensation seeking has been associated with violent behaviour in samples of undergraduate students (Derefinko et al, 2011;Dvorak et al, 2013;Miller et al, 2012) and violent prisoners (Shoham et al, 1989), and often observed in substance-using samples (Horvath et al, 2004;Knafo et al, 2013). However, greater disinhibition following benzodiazepine use (Paton, 2002) may also underlie benzodiazepine-related violence.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Lack of perseverance refers to failing to maintain focus on difficult or boring tasks33. It possesses the important relationship in decision making, for example, subjects with a low perseverance score learn more slowly in choosing from the good decks during the gambling task34.…”
Section: Discussionmentioning
confidence: 99%
“…Negative urgency refers to losing control over their behavior when experiencing strong negative emotions33. Individuals with a high level of negative urgency had a high tendency to engage in addictive behaviors, such as consumption of alcohol and drugs3940.…”
Section: Discussionmentioning
confidence: 99%